2015
DOI: 10.1016/s2095-4964(15)60181-9
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of Tuina techniques on working-related musculoskeletal disorder of professional orchestra musicians

Abstract: Although results showed that Tuina techniques are effectively reducing WRMD in professional orchestra musicians of the north of Portugal, further investigations with stronger measurements, double-blinding designs and bigger simple sizes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Of the 66 RCTs, 1 RCT was C(T)MT versus sham C(T)MT [40], 48 RCTs were C(T)MT versus other active interventions [5, 41–87], and 17 RCTs were C(T)MT plus other active interventions versus same other interventions [88–104] (Tables 1 and 3). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 66 RCTs, 1 RCT was C(T)MT versus sham C(T)MT [40], 48 RCTs were C(T)MT versus other active interventions [5, 41–87], and 17 RCTs were C(T)MT plus other active interventions versus same other interventions [88–104] (Tables 1 and 3). …”
Section: Resultsmentioning
confidence: 99%
“…Studies about extremity diseases/disorders were classified into upper ( n = 13) and lower extremity ( n = 11), including 5 studies about shoulder lesions [5, 73, 74, 98, 99], 8 about arm and hand disorders [75–81, 100], 8 about knee problems [82–85, 101104], and 2 about leg and foot disorders [86, 87]. One sham control study was a RCT that looked at overall musculoskeletal disorders, so it was not possible to classify it into a specific category [40]. Therefore, we have indicated the percentages for each part based on how the authors reported them in their study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations